Deregulating School Aid in California Revenues and Expenditures in the Second Year of Categorical Flexibility - Imazeki, Jennifer (RAND Corporation, 2012)
A large share of California's school funding is allocated through categorical programs whose funding is contingent on districts using the money in a particular way or for a particular purpose. In 2008-09, the strings were taken off 40 of these programs as part of a budget deal that also reduced the funding for those programs. This report describes statewide patterns in district revenues and expenditures in light of this new state policy.